2012
DOI: 10.1161/strokeaha.112.657742
|View full text |Cite|
|
Sign up to set email alerts
|

Stroke Assessment With Diffusional Kurtosis Imaging

Abstract: Background and Purpose Despite being the gold standard technique for stroke assessment, conventional diffusion magnetic resonance imaging (dMRI) provides only partial information about tissue microstructure. Diffusional kurtosis imaging (DKI) is an advanced dMRI method that yields, in addition to conventional diffusion information, the diffusional kurtosis (K), which may help improve characterization of tissue microstructure. In particular, this additional information permits the description of white matter (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

27
183
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 214 publications
(221 citation statements)
references
References 30 publications
27
183
0
6
Order By: Relevance
“…axonal beading). 38 In our study, we observed a significant relationship between cumulative exposure metrics and many of the DKI-derived and WMM metrics. These results indicate a variety of changes and injury types that may be occurring within the white matter, including axonal swelling, axonal beading, ischemia, and astrogliosis.…”
supporting
confidence: 51%
See 3 more Smart Citations
“…axonal beading). 38 In our study, we observed a significant relationship between cumulative exposure metrics and many of the DKI-derived and WMM metrics. These results indicate a variety of changes and injury types that may be occurring within the white matter, including axonal swelling, axonal beading, ischemia, and astrogliosis.…”
supporting
confidence: 51%
“…Similar changes have been seen previously in ischemic regions of stroke patients. 38,39 The significant increase in MK also has been demonstrated in axonal injury and astrogliosis.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…2 and the arrows indicate that CO 2 generated by tissue is cleared through blood vessels. (B) When the hypercapnic blood first arrives, arterial CO 2 concentration will increase, delivering extra CO 2 to the tissue.…”
Section: Disclosure/conflict Of Interestmentioning
confidence: 99%